High-dielectric high-breakdown-strength electrostatic chuck and preparation method thereof

By using high-dielectric constant ceramic dielectric layer material in electrostatic chuck, the problems of insufficient breakdown strength and insufficient adsorption force in high-voltage environments are solved, and firm adsorption of high-voltage resistivity materials and semiconductors are achieved Improved manufacturing accuracy and safety.

CN119208237AActive Publication Date: 2024-12-27GUANGDONG FINE CERAMICS NEW MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411358691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing electrostatic chucks have insufficient breakdown strength in high-voltage environments, making it difficult to firmly adsorb wafers with high volume resistivity, and there are purity and uniformity problems during the production process.

Method used

Using high dielectric constant ceramic dielectric layer materials, including aluminum oxide, aluminum nitride, barium titanate, barium zirconium titanate, lead niobium magnesium niobium and barium strontium titanate, to optimize the formulation and structure of the ceramic dielectric layer , increase the breakdown strength and dielectric constant, combine the organic bonding layer and the metal base to form an efficient electrostatic chuck.

Benefits of technology

It improves the adsorption force and stability of the electrostatic chuck, ensures safety in high-voltage environments, and achieves firm adsorption of high-volume resistivity materials, improving the accuracy and quality of semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208237A_ABST
    Figure CN119208237A_ABST
Patent Text Reader

Abstract

The invention relates to a high-dielectric high-breakdown-strength electrostatic chuck and a preparation method thereof. The electrostatic chuck comprises a ceramic dielectric layer, a bonding layer and a metal base which are sequentially arranged from top to bottom, the ceramic dielectric layer comprises at least one ceramic dielectric layer, and raw materials of the ceramic dielectric layer comprise at least one of aluminum oxide and aluminum nitride and at least one of barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate. According to the electrostatic chuck, the electrostatic adsorption technology is utilized, efficient electrostatic adsorption is achieved through a high-dielectric-constant ceramic dielectric layer material, and the high-dielectric-constant material can effectively store charges, so that the electrostatic adsorption force is enhanced, and workpieces such as wafers and the like keep better stability and precision in the machining process; and the ceramic dielectric layer material has high breakdown strength, so that the working safety of the electrostatic chuck in a high-voltage environment can be ensured. The preparation method is convenient to control, high in production efficiency and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor ceramics, and in particular to an electrostatic chuck with high dielectric and high breakdown strength and a preparation method thereof. Background Art

[0002] The working principle of the electrostatic chuck is based on the adsorption effect of electrostatic force. By applying a high-voltage electric field, the working surface is positively charged, and the workpiece is negatively charged, thereby generating an electrostatic attraction, so that the workpiece is closely attached to the working surface. It has been widely used in semiconductor process, such as etching, chemical vapor deposition, ion implantation, etc. During wafer processing, by applying a charge on the electrode surface of the electrostatic chuck, an electrostatic force is generated, so that the wafer is adsorbed and fixed on the chuck surface by the electrostatic force. This adsorption method is suitable for vacuum environment or plasma environment, which can keep the wafer flat and suppress the deformation of the wafer during the process, so as to improve the stability and reliability of the wafer processing process. However, in the manufacturing process, a high-voltage power supply is often required to control the temperature and position of the wafer. Therefore, the electrostatic chuck needs to be able to withstand higher voltages without breakdown, and the electrostatic chuck often has the problem of insufficient adsorption firmness for wafers with high volume resistivity, which needs to be solved. Summary of the invention

[0003] In order to solve the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide an electrostatic chuck with high dielectric and high breakdown strength. The electrostatic chuck utilizes electrostatic adsorption technology to achieve efficient electrostatic adsorption through a ceramic dielectric layer material with a high dielectric constant. The high dielectric constant material can effectively store charge, thereby enhancing the electrostatic adsorption force, so that workpieces such as wafers maintain better stability and precision during the processing, and the ceramic dielectric layer material has a high breakdown strength, which is beneficial to ensure the safety of the electrostatic chuck working in a high-voltage environment.

[0004] Another object of the present invention is to provide a method for preparing an electrostatic chuck with high dielectric constant and high breakdown strength. The preparation method is easy to control, has high production efficiency, and is conducive to large-scale production. The prepared electrostatic chuck uses a ceramic dielectric layer with high dielectric constant and high breakdown strength, and is safe and reliable to use.

[0005] The object of the present invention is achieved through the following technical solution: an electrostatic chuck with high dielectric and high breakdown strength comprises a ceramic dielectric layer, a bonding layer and a metal base arranged in sequence from top to bottom, the ceramic dielectric layer comprises at least one ceramic dielectric layer, the raw materials of the ceramic dielectric layer comprise at least one of aluminum oxide (Al2O3) and aluminum nitride (AlN), and comprise barium titanate (BaTiO3), barium zirconate titanate (BaZr 0.2 Ti 0.8 O3), lead magnesium niobate (MgNb4O 12At least one of Pb) and barium strontium titanate (BaSr(TiO3)2).

[0006] The electrostatic chuck in the present invention mainly includes three parts: a ceramic dielectric layer, an adhesive layer and a metal base. The ceramic dielectric layer, as the core component of the electrostatic chuck, plays a decisive role in the adsorption force and temperature uniformity of the electrostatic chuck. The metal base mainly provides assembly, load-bearing and temperature control functions; the adhesive layer is located between the ceramic dielectric layer and the metal base to firmly bond the two. The present invention optimizes the ceramic material and structure of the ceramic dielectric layer, increases the breakdown strength and dielectric constant of the ceramic dielectric layer through formula adjustment and structural improvement, and can achieve the electrostatic chuck to firmly adsorb high volume resistivity objects including sapphire, glass, etc., solve the problem that the prior art is difficult to achieve electrostatic adsorption of wafers with high volume resistivity, replace mechanical clamping, and improve product processing yield.

[0007] Furthermore, the ceramic dielectric layer comprises the following raw materials in parts by weight: 50-90 parts of aluminum oxide, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

[0008] Furthermore, the ceramic dielectric layer comprises the following raw materials in parts by weight: 50-90 parts of aluminum nitride, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

[0009] Furthermore, the bonding layer is an organic bonding layer, and the material of the organic bonding layer is at least one of thermally conductive silicone and epoxy resin.

[0010] Furthermore, the ceramic dielectric layer includes a first ceramic dielectric layer, an adsorption electrode layer, a second ceramic dielectric layer, a heating layer and a third ceramic dielectric layer which are arranged in sequence from top to bottom, and the third ceramic dielectric layer is arranged on the upper end surface of the metal base; the electrostatic chuck is also provided with a plurality of helium holes, and the helium holes penetrate the lower surface and the upper surface of the ceramic dielectric layer from bottom to top, and the upper surface of the first ceramic dielectric layer is provided with a plurality of protrusions protruding upward.

[0011] Furthermore, the metal base is provided with a coolant channel and a helium channel connected to multiple helium holes, and the helium channel is ring-shaped; the adsorption electrode layer and the heating layer are respectively provided with an adsorption electrode lead-out terminal and a heating electrode lead-out terminal, and the adsorption electrode lead-out terminal and the heating electrode lead-out terminal both extend downward to the lower end of the metal base; the metal base is provided with an adsorption electrode channel for the adsorption electrode lead-out terminal to pass through, and a heating electrode channel for the heating electrode lead-out terminal to pass through.

[0012] Another object of the present invention is achieved through the following technical solution: A method for preparing the above-mentioned high-dielectric and high-breakdown strength electrostatic chuck comprises the following steps: bonding a ceramic dielectric layer to a metal base through an adhesive layer to form an electrostatic chuck.

[0013] Furthermore, the method for preparing the ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: according to the raw material composition of the ceramic dielectric layer, aluminum oxide or aluminum nitride and at least one of barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are taken and mixed in proportion to obtain a mixed powder; then, 90-161 parts of the mixed powder, 3-7 parts of a sintering aid, 45-55 parts of a solvent and 0.5-2.5 parts of a dispersant are put into a ball mill for ball milling; then, 7-11 parts of a binder and 4-8 parts of a plasticizer are added and the ball milling is continued; then, the ball-milled slurry is degassed to obtain a tape casting slurry with a viscosity of 5000-10000 mPa.s; the particle size of the aluminum oxide, aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate is 0.2-3 μm; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape, which is then cut into multiple ceramic green sheets; (3) Punching: Processing structural holes and positioning hole structures on ceramic raw tiles; (4) Printing and filling holes: Printing and filling holes with metal slurry on the surface of the punched ceramic green tile using a printing and filling machine; the metal slurry mainly includes tungsten, molybdenum and their alloys, and its main function is to provide a conductive path and generate heat; (5) Lamination: stacking the printed ceramic green sheets and then sealing them with plastic; then pressing the sealed stacked sheets to obtain ceramic green plates; (6) Debinding: Place the ceramic green plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it warm for 3-6 hours to obtain a ceramic debinding sheet; (7) Sintering: Sintering the ceramic stripping sheet at high temperature to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is machined to obtain a ceramic dielectric layer.

[0014] The present invention optimizes the ceramic material formula and process of the ceramic dielectric layer of the electrostatic chuck, improves the dispersibility of the ceramic material powder, reduces the grain size of the alumina or aluminum nitride ceramic, improves the thermal properties, electrical properties, and mechanical properties of the alumina or aluminum nitride ceramic dielectric layer, and reduces the temperature required for sintering, thereby solving the problems that the prior art cannot prepare ultra-high purity alumina or aluminum nitride ceramics, and the products have low strength, poor uniformity, poor quality consistency, and are difficult to sinter.

[0015] Furthermore, in step (1), aluminum oxide, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of SiO2, CaO and MgO; in step (7), the ceramic debonding sheet is loaded into a high-temperature sintering furnace and sintered at 1500-1650°C for 2-4 hours to obtain a sintered ceramic plate.

[0016] Furthermore, in step (1), aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of CeO2, CaO, CaF2 and Y2O3; in step (7), the ceramic debonding sheet is loaded into a high-temperature sintering furnace and sintered at 1750-1850°C for 2-4 hours to obtain a sintered ceramic plate.

[0017] Furthermore, in step (1), the solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol, and butanone; the dispersant is at least one of castor oil, brown fish oil, polyethylene glycol, and phosphate ester; the binder is polyvinyl butyral; and the plasticizer is at least one of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.

[0018] The beneficial effects of the present invention are: (1) The electrostatic chuck of the present invention utilizes electrostatic adsorption technology when in use, and realizes efficient electrostatic adsorption by adopting a ceramic dielectric layer of a high dielectric constant ceramic material; the ceramic dielectric layer of the electrostatic chuck has high breakdown strength and high dielectric constant. The high dielectric constant ceramic dielectric layer can better store charge, increase the electric field strength, and have low dielectric loss, so that the electrostatic chuck has a sufficiently strong adsorption force to fix the low conductivity material to prevent it from moving or falling off during the processing, thereby ensuring the precision and quality of semiconductor manufacturing; the high breakdown strength characteristic ensures the safety of the electrostatic chuck working in a high-voltage environment. In the semiconductor manufacturing process, a high-voltage power supply is often required to control the temperature and position of the chip. The electrostatic chuck with a high breakdown strength can withstand higher voltages without breakdown, thereby ensuring the stability and safety of the processing process.

[0019] (2) The preparation method is easy to control, has high production efficiency, and is conducive to large-scale production; the prepared electrostatic chuck uses a ceramic dielectric layer with a high dielectric constant and high breakdown strength, and is safe and reliable to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the three-dimensional structure of the electrostatic chuck of the present invention.

[0021] Figure 2is a top view of the electrostatic chuck of the present invention.

[0022] Figure 3 It is a cross-sectional view of the electrostatic chuck of the present invention.

[0023] Figure 4 yes Figure 3 Enlarged view of point A in the middle.

[0024] Figure 5 It is a schematic diagram of the structure of the heating layer.

[0025] Figure 6 It is a schematic diagram of the structure of the adsorption electrode layer.

[0026] The figures are marked as follows: 11, metal base; 12, first ceramic dielectric layer; 13, second ceramic dielectric layer; 14, third ceramic dielectric layer; 15, adsorption electrode layer; 16, heating layer; 17, helium hole; 18, helium channel; 19, coolant channel; 20, adsorption electrode channel; 21, heating electrode channel; 22, heating circuit; 23, adsorption electrode. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0028] like Figure 1-6 As shown, in one embodiment of the present invention, a high dielectric and high breakdown strength electrostatic chuck includes a ceramic dielectric layer, a bonding layer and a metal base 11 arranged in sequence from top to bottom.

[0029] In one embodiment of the present invention, the ceramic dielectric layer includes a first ceramic dielectric layer 12, an adsorption electrode layer 15, a second ceramic dielectric layer 13, a heating layer 16 and a third ceramic dielectric layer 14 arranged in sequence from top to bottom, and the third ceramic dielectric layer 14 is arranged on the upper end surface of the metal base 11; the electrostatic chuck is also provided with a plurality of helium holes 17 distributed at intervals, and the helium holes 17 penetrate the lower surface and the upper surface of the ceramic dielectric layer from bottom to top, and the upper surface of the first ceramic dielectric layer 13 is provided with a plurality of protrusions protruding upward and distributed at intervals, providing support for the wafer and the circulation of the helium channel 18. The helium holes 17 penetrate the third ceramic dielectric layer 14, the heating layer 16, the second ceramic dielectric layer 13, the adsorption electrode layer 15, and the first ceramic dielectric layer 12 in sequence upward from the metal base.

[0030] Furthermore, the metal base 11 is provided with a cooling liquid channel 19 and a helium channel 18 connected with a plurality of helium holes 17, and the helium channel 18 is annular; the adsorption electrode layer 15 and the heating layer 16 are respectively provided with an adsorption electrode lead-out terminal and a heating electrode lead-out terminal, and the adsorption electrode lead-out terminal and the heating electrode lead-out terminal both extend downward to the lower end of the metal base 11; the metal base 11 is provided with an adsorption electrode channel 20 for the adsorption electrode lead-out terminal to pass through, and a heating electrode channel 21 for the heating electrode lead-out terminal to pass through. The cooling liquid channel 19 can be set as a one-in-one-out spiral layout and a multi-in-multi-out dispersed array layout; that is, it can be set as a spiral layout with one inlet and one outlet and a dispersed array layout with multiple outlets and multiple inlets. The material of the metal base 11 is stainless steel or aluminum.

[0031] In some embodiments of the present invention, the ceramic dielectric layer includes the following raw materials in parts by weight: 50-90 parts of aluminum oxide, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

[0032] In some embodiments of the present invention, the ceramic dielectric layer includes the following raw materials in parts by weight: 50-90 parts of aluminum nitride, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

[0033] In some embodiments of the present invention, the ceramic dielectric layer further comprises 3-7 parts of a sintering aid.

[0034] In some embodiments of the present invention, the bonding layer is an organic bonding layer, and the material of the organic bonding layer is at least one of thermally conductive silicone and epoxy resin. The thermally conductive silicone and epoxy resin are materials in the prior art and are used to bond the ceramic dielectric layer and the metal base 11.

[0035] In an embodiment of the present invention, a method for preparing an electrostatic chuck with high dielectric and high breakdown strength includes the following steps: bonding a ceramic dielectric layer to a metal base 11 through an adhesive layer to prepare an electrostatic chuck.

[0036] In some embodiments of the present invention, the method for preparing the ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: according to the raw material composition of the ceramic dielectric layer, aluminum oxide or aluminum nitride and at least one of barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; then, 90-161 parts of the mixed powder, 3-7 parts of a sintering aid, 45-55 parts of a solvent and 0.5-2.5 parts of a dispersant are put into a ball mill containing 200-300 parts of aluminum oxide pellets for ball milling at a speed of 40-70 r / min for 12-24 hours; then, 7-11 parts of a binder and 4-8 parts of a plasticizer are added to the ball mill and the ball milling is continued for 12-24 hours; then, the ball milled slurry is degassed for 1-2 hours to obtain a slurry adhered to 5000-10000 mPa.s casting slurry; the purity of the aluminum oxide, aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate is 99.9%, and the particle size is 0.2-3μm; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3-0.6 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine; (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic green tile; (4) Printing and filling holes: After the holes are punched, the surface of the green ceramic sheet is printed with metal paste and the holes are filled with the metal paste using a printing and filling machine. The main components of the metal paste include tungsten, molybdenum and their alloys, and their main functions are to provide a conductive path and generate heat. The metal paste can be tungsten, molybdenum and their alloys in the prior art. (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 60-80°C and 10-40MPa for 10-30 minutes to obtain a ceramic green sheet; (6) Debinding: Place the ceramic green plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it warm for 3-6 hours to obtain a ceramic debinding sheet; (7) Sintering: Sintering the ceramic stripping sheet at high temperature to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain a ceramic dielectric layer with a flatness of <5 μm and a surface roughness of <0.1 μm.

[0037] In some embodiments of the present invention, in step (1), aluminum oxide, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of SiO2, CaO and MgO; in step (7), the ceramic debonding sheet is loaded into a high-temperature sintering furnace and sintered at 1500-1650°C for 2-4 hours to obtain a sintered ceramic plate.

[0038] Furthermore, in step (1), aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of CeO2, CaO, CaF2 and Y2O3; in step (7), the ceramic debonding sheet is loaded into a high-temperature sintering furnace and sintered at 1750-1850°C for 2-4 hours to obtain a sintered ceramic plate.

[0039] Furthermore, in step (1), the solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol, and butanone; the dispersant is at least one of castor oil, brown fish oil, polyethylene glycol, and phosphate ester; the binder is polyvinyl butyral; and the plasticizer is at least one of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.

[0040] Example 1 like Figure 1-6 As shown, in this embodiment, a high dielectric and high breakdown strength electrostatic chuck includes a ceramic dielectric layer, a bonding layer and a metal base 11 arranged in sequence from top to bottom; the ceramic dielectric layer includes a first ceramic dielectric layer 12, an adsorption electrode layer 15, a second ceramic dielectric layer 13, a heating layer 16 and a third ceramic dielectric layer 14 arranged in sequence from top to bottom, and the third ceramic dielectric layer 14 is arranged on the upper end surface of the metal base 11; the electrostatic chuck is also provided with a plurality of helium holes 17 distributed at intervals, and the helium holes 17 penetrate the lower surface and the upper surface of the ceramic dielectric layer from bottom to top, and the upper surface of the first ceramic dielectric layer 13 is provided with a plurality of protrusions protruding upward and distributed at intervals, providing support for the wafer and helium channel 18 circulation. The bonding layer is an organic bonding layer, and the material of the organic bonding layer is thermally conductive silicone. The material of the metal base 11 is stainless steel.

[0041] Furthermore, the metal base 11 is provided with a coolant channel 19 and a helium channel 18 connected to multiple helium holes 17, and the helium channel 18 is annular; the adsorption electrode layer 15 and the heating layer 16 are respectively provided with an adsorption electrode lead-in terminal and a heating electrode lead-in terminal, and the adsorption electrode lead-in terminal and the heating electrode lead-in terminal both extend downward to the lower end of the metal base 11; the metal base 11 is provided with an adsorption electrode channel 20 for the adsorption electrode lead-in terminal to pass through, and a heating electrode channel 21 for the heating electrode lead-in terminal to pass through.

[0042] When the electrostatic chuck of this embodiment is in use, the helium channel 18 and the helium hole 17 form a helium delivery passage, and the external helium can enter the metal base 11 and the ceramic dielectric layer through the helium channel 18 and the helium hole 17, so as to realize the cooling of the electrostatic chuck and the wafer, better control the temperature of the wafer, and evenly transfer heat during wafer processing, which is beneficial to maintaining the stability and quality of the wafer.

[0043] Furthermore, the adsorption electrode layer 15 is provided with an adsorption electrode 23, and the adsorption electrode 23 is connected to the adsorption electrode lead-out end. The heating layer 16 is provided with a heating circuit 22, and the heating circuit 23 is connected to the heating electrode lead-out end. The coolant channel 19 is arranged in the metal base 11 and is located below the helium channel 18. The coolant channel 19 has a repeatedly tortuous structure, and an inlet and an outlet are respectively arranged at both ends of the coolant channel 19. The coolant channel 19 of this embodiment is arranged in a spiral layout with one inlet and one outlet. The coolant flows repeatedly and tortuously in the coolant channel 19, and can cooperate with the heating circuit 23 to control the temperature of the wafer.

[0044] Furthermore, the multiple helium holes 17 are distributed in a circular array and are located above the inner cavity of the helium channel 18. Helium can enter the multiple uniformly distributed helium holes 17 from the helium channel 18, which helps to make the temperature of the ceramic dielectric layer and the wafer surface uniform during wafer processing.

[0045] Furthermore, the ceramic dielectric layers, namely the first ceramic dielectric layer 12, the second ceramic dielectric layer 13 and the third ceramic dielectric layer 14, all include the following raw materials in parts by weight: 85 parts of aluminum oxide, 15 parts of barium titanate, 23 parts of barium zirconate titanate, 20 parts of lead magnesium niobate, and 18 parts of barium strontium titanate.

[0046] This embodiment also provides a method for preparing an electrostatic chuck with high dielectric and high breakdown strength, comprising the following steps: bonding a ceramic dielectric layer to a metal base 11 via an adhesive layer to prepare an electrostatic chuck.

[0047] Furthermore, the method for preparing the ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: According to the raw material composition of the ceramic dielectric layer, aluminum oxide (Al2O3), barium titanate (BaTiO3), barium zirconate titanate (BaZr 0.2 Ti 0.8 O3), lead magnesium niobate (MgNb4O 12Pb) and barium strontium titanate (BaSr(TiO3)2) are mixed in proportion to obtain a mixed powder; then, by weight, 161 parts of the mixed powder, 5 parts of a sintering aid, 50 parts of a solvent, and 1.5 parts of a dispersant are put into a ball mill equipped with 250 parts of alumina balls for ball milling at a speed of 50 r / min for 18 hours; then 8 parts of a binder and 6 parts of a plasticizer are added to the ball mill, and the ball milling is continued for 18 hours; the ball-milled slurry is degassed for 1.5 hours to obtain a tape-cast slurry with a viscosity of 5000-10000 mPa.s; the purity of the alumina, barium titanate, barium zirconate titanate, lead magnesium niobate, and barium strontium titanate is 99.9%, and the particle size is 0.2-3μm; the sintering aid is SiO2; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.5 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine; (3) Punching: Use a laser punching machine to process structural holes and positioning hole structures on the ceramic green tile; (4) Printing and filling holes: After punching, the surface of the raw ceramic sheet is printed with metal paste and filled with holes using a printing and filling machine. The main components of the metal paste include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat; (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 70°C and 30 MPa for 20 minutes to obtain a ceramic green sheet; (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, put it into an atmosphere resistance furnace, slowly heat it to 550°C at a heating rate of 0.6°C / min, and keep it at this temperature for 5 hours to obtain a ceramic debinding sheet; (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1600°C for 3 hours to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain a ceramic dielectric layer with a flatness of <5 μm and a surface roughness of <0.1 μm.

[0048] Furthermore, in step (1), the solvent is ethyl acetate; the dispersant is polyethylene glycol; the binder is polyvinyl butyral; and the plasticizer is dioctyl phthalate.

[0049] In Examples 2-10 of the present invention and Comparative Example 1, the composition and dosage ratio of the raw materials for preparing the ceramic dielectric layer are different from those in Example 1, and the rest of the contents are the same as those in Example 1.

[0050] In Examples 1-10 and Comparative Example 1, the weight parts of the raw materials of the ceramic dielectric layer are shown in Table 1 below:

[0051] The performance parameters of the ceramic dielectric layers in Examples 1-10 and Comparative Examples 1-2 are shown in Table 2 below:

[0052] It can be seen from Examples 1-10 and Comparative Example 1 that Al2O 3、 BaTiO3、BaZr 0.2 Ti 0.8 O3、MgNb4O 12 The adjustment of the formula of Pb and BaSr(TiO3)2 can improve the breakdown strength and dielectric constant of the ceramic dielectric layer, thereby improving its adsorption capacity. Example 1 shows higher breakdown strength, dielectric constant and adsorption capacity, with a breakdown strength of 31KV / mm, a dielectric constant of 101 and an adsorption capacity of 207gf / cm². The formula of the ceramic dielectric layer of Comparative Example 1 is mainly Al2O3, without adding BaTiO3 and BaZr 0.2 Ti 0.8 O3、MgNb4O 12 Pb and BaSr(TiO3)2 show lower breakdown strength, dielectric constant and adsorption force, with a breakdown strength of 15KV / mm, a dielectric constant of 9.8 and an adsorption force of 50gf / cm². Ceramic dielectric layer materials with high dielectric constants can better store charge, increase electric field strength, and have low dielectric loss, thus providing stronger adsorption force. Electrostatic chucks have strong enough adsorption force to fix low conductivity materials and prevent them from moving or falling off during processing, thereby ensuring the precision and quality of semiconductor manufacturing.

[0053] Embodiment 11 In this embodiment, the ceramic dielectric layers, namely the first ceramic dielectric layer 12, the second ceramic dielectric layer 13 and the third ceramic dielectric layer 14, all include the following raw materials in parts by weight: 80 parts of aluminum nitride, 17 parts of barium titanate, 25 parts of barium zirconate titanate, 20 parts of lead magnesium niobate, and 18 parts of barium strontium titanate.

[0054] Furthermore, the method for preparing the ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: According to the raw material composition of the ceramic dielectric layer, aluminum nitride (AlN), barium titanate (BaTiO3), barium zirconate titanate (BaZr 0.2 Ti 0.8 O3), lead magnesium niobate (MgNb4O 12Pb) and barium strontium titanate (BaSr(TiO3)2) are mixed in proportion to obtain a mixed powder; then, by weight, 160 parts of the mixed powder, 6 parts of a sintering aid, 50 parts of a solvent, and 2 parts of a dispersant are put into a ball mill equipped with 250 parts of alumina balls for ball milling at a speed of 50 r / min for 18 hours; then, 9 parts of a binder and 7 parts of a plasticizer are added to the ball mill, and the ball milling is continued for 18 hours; the ball-milled slurry is degassed for 1.5 hours to obtain a tape-cast slurry with a viscosity of 5000-10000 mPa.s; the purity of the aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate, and barium strontium titanate is 99.9%, and the particle size is 0.2-3μm; the sintering aid is CeO2; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.5 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine; (3) Punching: Use a laser punching machine to process structural holes and positioning hole structures on the ceramic green tile; (4) Printing and filling holes: After punching, the surface of the raw ceramic sheet is printed with metal paste and filled with holes using a printing and filling machine. The main components of the metal paste include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat; (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 70°C and 30 MPa for 25 minutes to obtain a ceramic green sheet; (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 550°C at a heating rate of 0.3-1°C / min, and keep it at this temperature for 56 hours to obtain a ceramic debinding sheet; (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1800°C for 3 hours to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain a ceramic dielectric layer with a flatness of <5 μm and a surface roughness of <0.1 μm.

[0055] The rest of Example 11 is the same as Example 1.

[0056] In Examples 12 to 20 of the present invention and Comparative Example 2, the composition and dosage ratio of the raw materials for preparing the ceramic dielectric layer are different from those in Example 11, and the rest of the contents are the same as those in Example 11.

[0057] In Examples 11-20 and Comparative Example 2, the weight parts of the raw materials of the ceramic dielectric layer are shown in Table 3 below:

[0058] The performance parameters of the ceramic dielectric layers in Examples 11-20 and Comparative Example 2 are shown in Table 4 below:

[0059] It can be seen from Examples 11-20 and Comparative Example 2 that AlN 、 BaTiO3、BaZr 0.2 Ti 0.8 O3、MgNb4O 12 Adjusting the formula of Pb and BaSr(TiO3)2 can improve the breakdown strength and dielectric constant of the ceramic dielectric layer, thereby improving its adsorption capacity. Example 11 shows higher breakdown strength, dielectric constant and adsorption capacity. Its breakdown strength is 32KV / mm, dielectric constant is 103, and adsorption capacity is 209gf / cm². The ceramic formula of Comparative Example 2 is mainly AlN, without adding BaTiO3 and BaZr 0.2 Ti 0.8 O3、MgNb4O 12 Pb and BaSr(TiO3)2 show lower breakdown strength, dielectric constant and adsorption force. Its breakdown strength is 16KV / mm, dielectric constant is 8.6, and adsorption force is 50gf / cm². 0.2 Ti 0.8 O3、MgNb4O 12 Pb, BaSr(TiO3)2 can improve its breakdown strength, dielectric constant, and adsorption. Ceramics with high dielectric constants can better store charge, increase electric field strength, and have low dielectric loss, thus providing stronger adsorption. Electrostatic chucks have strong enough adsorption to fix low-conductivity materials to prevent them from moving or falling off during processing, thereby ensuring the precision and quality of semiconductor manufacturing.

[0060] The electrostatic chuck of the present invention utilizes electrostatic adsorption technology to achieve efficient electrostatic adsorption through high dielectric constant materials. High dielectric constant materials can effectively store charge, thereby enhancing the electrostatic adsorption force, so that workpieces such as wafers maintain better stability and precision during processing. In addition, the high breakdown strength characteristic ensures the safety of the electrostatic chuck working in a high-voltage environment. In the semiconductor manufacturing process, a high-voltage power supply is often required to control the temperature and position of the wafer. An electrostatic chuck with a high breakdown strength can withstand higher voltages without breakdown, thereby ensuring the stability and safety of the processing process.

[0061] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.

Claims

1. An electrostatic chuck with high dielectric and high breakdown strength, characterized in that: The invention comprises a ceramic dielectric layer, a bonding layer and a metal base which are arranged in sequence from top to bottom. The ceramic dielectric layer comprises at least one ceramic dielectric layer. The raw materials of the ceramic dielectric layer comprise at least one of aluminum oxide and aluminum nitride, and comprise at least one of barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate.

2. The high dielectric and high breakdown strength electrostatic chuck according to claim 1, characterized in that: The ceramic dielectric layer comprises the following raw materials in parts by weight: 50-90 parts of aluminum oxide, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

3. The high dielectric and high breakdown strength electrostatic chuck according to claim 1, characterized in that: The ceramic dielectric layer comprises the following raw materials in parts by weight: 50-90 parts of aluminum nitride, 5-25 parts of barium titanate, 5-25 parts of barium zirconate titanate, 5-20 parts of lead magnesium niobate, and 2-20 parts of barium strontium titanate.

4. The high dielectric and high breakdown strength electrostatic chuck according to claim 1, characterized in that: The ceramic dielectric layer includes a first ceramic dielectric layer, an adsorption electrode layer, a second ceramic dielectric layer, a heating layer and a third ceramic dielectric layer which are arranged in sequence from top to bottom, and the third ceramic dielectric layer is arranged on the upper end surface of the metal base; the electrostatic chuck is also provided with a plurality of helium holes, and the helium holes penetrate the lower surface and the upper surface of the ceramic dielectric layer from bottom to top, and the upper surface of the first ceramic dielectric layer is provided with a plurality of protrusions protruding upward.

5. The high dielectric and high breakdown strength electrostatic chuck according to claim 4, characterized in that: The metal base is provided with a coolant channel and a helium channel connected to a plurality of helium holes, and the helium channel is ring-shaped; the adsorption electrode layer and the heating layer are respectively provided with an adsorption electrode lead-out terminal and a heating electrode lead-out terminal, and the adsorption electrode lead-out terminal and the heating electrode lead-out terminal both extend downward to the lower end of the metal base; the metal base is provided with an adsorption electrode channel for the adsorption electrode lead-out terminal to pass through, and a heating electrode channel for the heating electrode lead-out terminal to pass through.

6. A method for preparing an electrostatic chuck with high dielectric strength and high breakdown strength according to any one of claims 1 to 5, characterized in that The method comprises the following steps: bonding a ceramic dielectric layer and a metal base through a bonding layer to form an electrostatic chuck.

7. The method for preparing a high dielectric and high breakdown strength electrostatic chuck according to claim 6, characterized in that: The method for preparing the ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: according to the raw material composition of the ceramic dielectric layer, aluminum oxide or aluminum nitride and at least one of barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; then, by weight, 90-161 parts of the mixed powder, 3-7 parts of a sintering aid, 45-55 parts of a solvent and 0.5-2.5 parts of a dispersant are put into a ball mill for ball milling; then, 7-11 parts of a binder and 4-8 parts of a plasticizer are added and the ball milling is continued; then, the ball-milled slurry is degassed to obtain a casting slurry; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape, which is then cut into multiple ceramic green sheets; (3) Punching: Processing structural holes and positioning hole structures on ceramic green sheets; (4) Printing and filling holes: Use a printing and filling machine to print and fill holes with metal slurry on the surface of the punched ceramic green tile; (5) Lamination: stacking the printed ceramic green sheets and then sealing them with plastic; then pressing the sealed stacked sheets to obtain ceramic green plates; (6) Debinding: heating the green ceramic plate to debind the plate, thereby obtaining a debinding ceramic sheet; (7) Sintering: Sintering the ceramic stripping sheet at high temperature to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is machined to obtain a ceramic dielectric layer.

8. The method for preparing a high dielectric and high breakdown strength electrostatic chuck according to claim 7, characterized in that: In step (1), aluminum oxide, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of SiO2, CaO and MgO.

9. The method for preparing a high dielectric and high breakdown strength electrostatic chuck according to claim 7, characterized in that: In step (1), aluminum nitride, barium titanate, barium zirconate titanate, lead magnesium niobate and barium strontium titanate are mixed in proportion to obtain a mixed powder; the sintering aid is at least one of CeO2, CaO, CaF2 and Y2O3.

10. The method for preparing an electrostatic chuck with high dielectric and high breakdown strength according to claim 7, characterized in that: In step (1), the dispersant is at least one of castor oil, brown fish oil, polyethylene glycol and phosphate; the plasticizer is at least one of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate and diisononyl phthalate.

Citation Information

Patent Citations

  • Electrostatic chuck and method of forming it

    CN101884161A

  • BME multilayer ceramic capacitor, BME ceramic dielectric capacitor ceramic material and preparation method

    CN111646792A

  • AlN electronic ceramic material with high dielectric property

    CN113563085A

  • Electrostatic chuck and preparation method thereof

    CN117198967A

  • Aluminum nitride electrostatic chuck and preparation method thereof

    CN118619683A